The Interplay of Sensemaking and Material Artefacts during Interventions: A Case Study - Abildgaard, Johan Simonsen; Nielsen, Karina (Nordic Journal of Working Life Studies, 2018)
This study focuses on the interplay of different aspects of organization during work environment interventions. Specifically how the interplay of collective sensemaking, and material artefacts influence an intervention. We analyze an organization-level psychosocial work environment intervention conducted in two postal areas in the Danish Postal service. It provides a case study of the dynamics of a work environment intervention by focusing on how the intervention affects the organization, how sensemaking and materiality in the organization interact during the intervention is implemented, and how the intervention in turn is affected by the materiality and sensemaking of the organization. The present study adds to the current literature by demonstrating the role of sensemaking and materiality in interventions. The paper ends with a discussion of the links between sensemaking and sociomaterial artifacts and what role they play during work environment interventions, suggesting that interventions needs to align with both to be successful.